Compressibilidade de resíduos sólidos urbanos devido aos processos de biodegradação em um aterro sanitário - Salamoni, Gabriela Pippi Denardin (2019)
The municipal solid waste (MSW) contain a high content of organic matter, which generates leachate and gases due to biodegradation processes, resulting in settlements. Storage capacity and slope stability are among the most significant engineering concerns in the operation of MSW landfills. The research aims to study the compressibility behavior of MSW based on results of tests and monitoring carried out in phase D2/4 (89,990m³ and 97,324t) of the landfill of the Caturrita Waste Treatment Plant in Santa Maria/RS. By means of the characterization and analysis of the parameters, it tries to establish a relation between the evolution of the mechanisms involved in the compressibility of these waste and the mechanical, biodegradation and climatic aspects. It was made the instrumentation of this phase (measures of settlement), characterization of the base layer and the cover layer, of the wastes (gravimetry, moisture content, STV, temperature), of the leachate (temperature, pH, BOD5, COD, microbiology, metals), and biogas (volume, composition, temperature). In the compressibility evaluation, was used mathematical methods, rheological methods, methods based on soil mechanics and methods that take into account biodegradation. The gravimetric composition of MSW showed organic matter variation between 31.2 and 64.5%, with an average value of 46.1% (wet basis). The specific weight of MSW after compaction, values obtained in situ, ranged from 6.0 to 14.0kN/m³, with a mean value of 10.0kN/m3 (indicative of good compaction). The external temperature did not influence the temperature of the waste mass, which presented average temperature in the range of 39.0°C. The values found during the monitoring of the leachate refer the landfill to the methanogenic phase. The pH of the leachate ranged from 7.7 to 9.2, remaining within a range of 8.0 after 400 days of monitoring. Practically all the analyzed elements presented, with the time of grounding, a considerable reduction in their concentrations. Among other factors, this behavior is associated with the phases of the degradation process. The peak of methane generation occurred around 303 days, with a value equal to 180.0Nm³/h. The 06 benchmarks installed at the top of the D2/4 phase (SM5, SM6, SM17, SM18, SM19 and SM20) showed settlement equal to: 5.1m, 5.0m, 10.5m, 13.5m, 8.2m and 8.0m, with deformations corresponding to 32.7%, 31.4%, 40.6%, 32.1%, 48.1% and 49.1%. In relation to the mathematical models, they need a series of measured data, and many of the parameters have no physical meaning, and although they have presented high values of R2 (since they were adjusted to the measured values), when extrapolated the results are not consistents. Models of compressibility of residues were evaluated, regarding the statistical significance, practicality of application of the model and extrapolation to represent future settlement. Among the selected models, the model proposed by Gourc et al. (2010) can be considered the most practical because it requires a low number of parameters and presented a high statistical performance for forecast (R2 = 0.996). A new proposal was made with the purpose of hone the method from the consideration of fractions of food, garden waste and leather.